Integration of nanoporous structure into vertical organic field effect transistor / Muhammad Zharfan Mohd Halizan - Muhammad Zharfan , Mohd Halizan (2018)
Since the last three decades, a lot of endeavours have been done by researchers to enhance the performance of Organic Field Effect Transistor (OFET) by altering the organic semiconductors properties through modifying the molecular/monomeric units or doping the semiconductor materials. The challenges are to increase the output current, to increase the ON/OFF ratio and to decrease the turn on voltage. Vertical Organic Field Effect Transistor (VOFET) is a new structure of OFET which has the vertical structure instead of lateral. By having the vertical designation, this type of transistor enabled to have way smaller channel length between drain and source which is in nanoscale compared to lateral OFET’s microscale. The current industrial market is focusing on the lateral OFET and therefore, by providing the alternative of vertical structure of organic material-based transistor, the enhancement can be achieved. For the first phase, the fabrication of in-situ anodic alumina template (AAO) directly onto glass substrate is realized. Uniformity and density of pore size, can be respectively tuned by varying the stirring speeds (0 – 300 rpm) and molarity of pore widening agent (0 – 10 % of phosphoric acid). Consequently, template with 100 rpm stirring rate has a better uniformity with 1540 pores compared to 0, 50 and 200 rpm. Furthermore, the pore widening technique using phosphoric acid is studied by varying its concentrations. Occurrence of merging pores is observed by increasing the molarity of acid to 10 % which unlikely to happen in the lower molarity of 5 % phosphoric acid. Porous alumina template will then be used to infiltrate vanadyl 2, 9, 16, 23-tetraphenoxy- 29H, 31H-phthalocyanine (VOPcPhO) prior to the formation of alumina:VOPcPhO nanocomposite. Studies of template production on top of different substrates are done with glass and ITO substrates. As the result, both of these substrates produced templates with almost similar total number of pores of 1540 and 1455 for glass and ITO substrate, respectively. In the second part, this work aims at improving the performance of VOFET by synthesizing the different morphology of dielectric layer; porous and non-porous to be used in the fabrication of 3-dimensional (3D) VOFET. To produce the 3D VOFET, porous alumina template is applied as to allow the replicating process between the template and P(VDF-TrFE) to occur. It is found that the replicating process has generated the porous structure of P(VDF-TrFE). The study on the VOFET fabrication is done where the preparation of dielectric layer (copolymer P(VDF-TrFE)), spin coating of silver nanowire, semiconducting material (VOPcPhO) and deposition of aluminium are carried out. Two systems are prepared in this study; (i) thin film copolymer (without the application of alumina template) and (ii) nanostructured copolymer (with the application of alumina template). VOFET without the porous has the current of 3.5 × 10−4 A obtained at drain-source voltage (VDS) of 25 V with the turn-on voltage of 10 V. Meanwhile, the VOFET integrated with porous recorded a better current of 2.0 × 10−3 A at VDS of 25 V with the turn-on voltage of 7 V. The novelty of this work is, the fabrication of nanostructured copolymer and its integration into VOFET which has enhanced the output currents and turn on voltages.